Evaluation of The Importance of Sensory Plate to Analyze the Pre and Post Rehab Effect of Exercise on Knee Health in Patient with Total Knee Replacement - Bohra, Mustafa; Khan, Jafar; Shandilya, Anurodh; Sharma, Subash; Gupta, Sujay; Pinjara, Farukh Mohammad; Pal, Renuka; Chauhan, Tina; Sharma, Deepak; Ramawat, Prashant (Journal of Neonatal Surgery, 2025)
Background: Total knee replacement (TKR) is one of the most widely performed surgical interventions for end-stage knee osteoarthritis, offering substantial improvements in pain relief and mobility. However, despite successful surgical outcomes, many patients continue to experience challenges in balance, proprioception, and postural control during postoperative recovery. Conventional rehabilitation programs primarily focus on strength and flexibility but often fail to address subtle deficits in neuromuscular coordination. Recent advancements in baropodometric and sensory plate systems provide an opportunity to objectively measure balance parameters, load distribution, and centre of pressure shifts, thereby offering valuable insights into postural rehabilitation after TKR. Aim: The present study aimed to evaluate the effectiveness of exercise-based rehabilitation in patients with total knee replacement using a sensory plate as an assessment and feedback tool. Methodology: This experimental study recruited patients who had undergone unilateral TKR. Participants underwent a structured exercise program focusing on strength, flexibility, and proprioceptive training over a defined intervention period. Pain was assessed using the Numerical Pain Rating Scale (NPRS), while balance and postural control were measured using a sensory plate, analyzing parameters such as barycenter alignment, centre of pressure (C.O.P.) displacement, and plantar load distribution. Pre- and post-intervention assessments were compared to determine rehabilitation effectiveness. Results: Post-intervention analysis demonstrated a significant reduction in pain levels (as measured by NPRS) and marked improvements in postural control indices recorded on the sensory plate. Participants showed better load symmetry, reduced sway, and improved barycenter alignment following the exercise program. These findings suggest that integrating sensory feedback into rehabilitation enhances functional recovery in post-TKR patients. Conclusion: Exercise-based rehabilitation significantly improves pain and balance in patients following TKR. The use of sensory plates provides an objective and reliable means of assessing postural control, thereby bridging the gap between subjective symptom reporting and measurable functional outcomes. Incorporating such technology-driven tools into rehabilitation may optimize recovery strategies and contribute to improved quality of life after TKR.